The Making of a Creative City as a Viable Service System - Maryunani, Salfitrie; Simatupang, Togar; Mirzanti , Isti; Windasari, Nila A (Research Synergy Foundation, 2025)
The concept of a creative city has been influential for decades, yet its definition remains elusive, hindering the development of effective strategies for urban revitalization. This study addresses this challenge by reframing the creative city as a complex service system. This perspective emphasizes the intricate interplay between diverse actors, resources, and processes that contribute to the city's cultural and economic vibrancy. Focusing on Bandung, Indonesia, the research utilizes a cultural mode of production model to assess the city's cultural assets. This framework considers the interconnectedness of cultural production, consumption, and distribution, recognizing the crucial role of both formal and informal networks. Employing a mixed-methods approach that combines in-depth interviews with netnography analysis, the study aims to develop a nuanced understanding of Bandung's creative ecosystem, propose a framework for assessing the